2015
DOI: 10.17352/2455-3484.000006
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Beverage Specific Alcohol Sale on Liver Cirrhosis Mortality in Russia

Abstract: Background: Liver cirrhosis is a major cause of deaths in many developed countries. There is evidence that beverage preference may have modifying influence on liver cirrhosis risk independently of the amount of alcohol consumed.The aim of this study was to examine the relation between the consumption of different beverage types and liver cirrhosis mortality rates in Russia.Method: Time-series analytical modeling techniques were used to examine the relation between the sale of different alcoholic beverages (vod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Overall, consumption is lower, but spirits are the most popular type of alcohol drinking among Thai community. Razvodovsky (2015) conducted a nationwide study in Russia to examine the relation between the consumption of different beverage types and liver cirrhosis mortality rates in Russia. The investigator found that spirits was the key beverage driving the association between being diagnosed with liver cirrhosis.…”
Section: Characteristics Of the Study Participantsmentioning
confidence: 99%
“…Overall, consumption is lower, but spirits are the most popular type of alcohol drinking among Thai community. Razvodovsky (2015) conducted a nationwide study in Russia to examine the relation between the consumption of different beverage types and liver cirrhosis mortality rates in Russia. The investigator found that spirits was the key beverage driving the association between being diagnosed with liver cirrhosis.…”
Section: Characteristics Of the Study Participantsmentioning
confidence: 99%